Metodologia para dimensionamento de um equipamento para secagem da vagem verde de soja e seus resíduos - Tunnermann, Herbert (2018)
The early harvest and the irregular maturity of soybeans result in a high number of green pods harvested along with dry pods. A great portion of these pods is separated in the pre-cleaner and the rest is stored with the grains in silos and warehouses. Green grains or pods contain more humidity than mature grains, which affects storage quality due to the potential contamination by fungi and bacteria. The acidity ratio and chlorophyll content increase because of the percentage of green pods, which results in cost increases for the processes of oil refining and production of protein products. On the other hand, there is a possibility of reusing the pods that were not threshed in the harvest, focusing on storage quality and financial results. Therefore, a research was performed on existing drying equipment and processes, and their sizing parameters for drying green soybeans and their residues. The great difficulty of drying green pods and their residues, besides the high humidity content, is to ensure a continuous flow during the drying process, because it is easy to occur "plugging" when this product is moving inside the dryer. Equipment sizing is based on thermodynamic laws to achieve a capacity of 6 tons per hour, reducing the green pods and their residues from 31% to 18%. The significant sizing for the study are drying air temperature and flow rate, diameter, length and rotation, and drum angle. The sizing performed in this study shows a drying air flow rate of 68,500 m³/h at a temperature of 80 degrees centigrade, and humidity may be reduced from 31% to 18% for a capacity of 6 tons per hour. For this condition, the drum should have 2.4 meters of diameter and 18 meters of length, and this rotating drum should be set at 6 rotations per minute and inclination of 5 degrees so that the dwelling time of the product in contact with the drying air is one hour. According to these drying parameters and dryer dimensions, the results obtained provide the capacity expected, allowing to dry the green soybeans and their residues in the model and dimensions of the dryer selected.